PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA WURYANI KONVEKSI - Romadon, Ahmad Sahri; Syafitri, Laela Dhessy; Ningrum, Natalia Fitria (STIE PENA, 2023)
This study aims to determine the effect of education and job training on the work productivity of Wuryani Convection employees. In this study, the population was all employees of Wuryani Convection as many as 45 people. The type of data used is primary data and secondary data while data analysis uses multiple linear regression analysis. The results showed that the Education Variable had no significant effect on work productivity. Training variable is proven to have a positive effect on work productivity. Partially, the education variable has a positive and insignificant effect on work productivity. Partially, the training variable has a positive and significant effect on work productivity. Keywords :Education, Training, Work Productivity